"Integración de Herramientas Computacionales para la construcción de engranajes de Fotocopiadoras Ricoh – Serie 8000" - Mayo Mayo, Edison Gonzalo (2021)
In the present work, a theoretical and experimental study was carried out, three-dimensional reconstruction techniques are proposed using artificial vision with free software and hardware. The bibliographic review supports the applications of the analyzed works, insofar as it refers to computational tools for processing flat images (2D) such as the generation of an object in three dimensions (3D). The first stage of design consists of the analysis of the physical characteristics of the plastic gears of a Ricoh 8000 series photocopier. From the experimental study and a hierarchical analytical process, a characterization and selection of the most suitable gears to be built by means of techniques was obtained. of rapid prototyping with 3D printing, in addition, a static analysis of the reconstructed gear was carried out for a force of 1.7 Nm using the mechanical properties of polymers such as PLA (Polylactic Acid), PETG (Polyethylene Terephthalate) and ABS (Acrylonitrile Butadiene Styrene) obtaining a safety factor of 4.57, 4.63, and 4.73 respectively. A comparison was made between 3D printing techniques such as SLS (Stereolithography), SLA (Selective Laser Sintering) and FDM (Fused Wire Deposition). The gears obtained with the FDM rapid prototyping technique had a minimum error of 0.5% and a maximum of 2.5% between the real measurement and the reproduced one. The proposed methodology allows to reconstruct a CAD (Computer Aided Design) plastic gear, analyze its mechanical characteristics with different CAE (Computer Aided Engineering) materials and build it using 3D CAM (Computer Aided Manufacturing) printing techniques.